How do you simplify #(3/4)^-1# and write it using only positive exponents?

1 Answer
Mar 29, 2017

Answer:

#(3/4)^-1 = (4/3)^1# to write it using only positive exponents

Explanation:

The negative exponent in this expression requires that we invert the fraction, which is the same as taking the inverse of the value of the fraction.

The inverse of #3/4 = 1/(3/4) = 1/1*4/3 = 4/3#

Then;#(3/4)^-1 = (4/3)^1# to write it using only positive exponents

The final simplification would be: #(3/4)^-1 = (4/3)^1 = (4/3) = 1 1/3#